Electroacupuncture preconditioning reduces ROS generation with NOX4 down-regulation and ameliorates blood-brain barrier disruption after ischemic stroke. Issue 1 (December 2016) - Jung, Yeon; Lee, Sae-Won; Park, Jung; Seo, Hyung; Choi, Byung; Shin, Hwa
Abstract Background Electroacupuncture (EA) is a modern application based on combination of traditional manual acupuncture and electrotherapy that is frequently recommended as an adjuvant treatment for ischemic stroke. EA preconditioning can ameliorate blood-brain barrier (BBB) dysfunction and brain edema in ischemia-reperfusion injury; however, its mechanism remains unclear. This study investigated the preventive effects of EA preconditioning, particularly on BBB injury, followed by a transient middle cerebral artery occlusion (MCAO) model in mice. Results Mice were treated with EA (20 min) at Baihui (GV20) and Dazhui (GV14) acupoints once a day for 3 days before ischemic injury. Infarct volume, neurological deficits, oxidative stress, Evans blue leakage and brain edema were evaluated at 24 h after ischemia-reperfusion injury. EA preconditioning significantly decreased infarct volume and improved neurological function even after ischemic injury. In addition, both Evans blue leakage and water content were significantly reduced in EA preconditioned mice. Whereas the expression of tight junction proteins, ZO-1 and claudin-5, were remarkably increased by EA preconditioning. Mice with EA preconditioning showed the reduction of astrocytic aquaporin 4, which is involved in BBB permeabilization. In addition, we found that EA preconditioning decreased reactive oxygen species (ROS) in brain tissues after ischemic injury. The expression of NADPH oxidase 4 (NOX4), not NOX2, was significantly suppressed in EA preconditioned mice. Conclusions These results suggest that EA preconditioning improve neural function after ischemic injury through diminishing BBB disruption and brain edema. And, the reduction of ROS generation and NOX4 expression by EA preconditioning might be involved in BBB recovery. Therefore, EA may serve as a potential preventive strategy for patients at high risk of ischemic stroke.